A High‐Pressure Praseodymium Fluoride Borate Linking Multiple Structural Features of Apatite‐Type Compounds. Issue 7 (9th January 2019) - Glätzle, Matthias; Pitscheider, Almut; Oeckler, Oliver; Wurst, Klaus; Huppertz, Hubert
Abstract: Pr5 (BO4 )3− x (BO3 ) x (F, OH)2.67 O0.28 ( x ≈1.6), a boron‐containing fluoride‐oxoapatite‐like compound, was obtained by the application of high‐pressure/high‐temperature synthesis. It exhibits a superstructure of the apatite type with a tripled c lattice parameter (space group P 63 / m ) and shows complex anion disorder along the 63 screw axis and occupation of distorted octahedra, as well as almost trigonal planar sites, by oxygen and fluorine atoms. Furthermore, a distinct BO4 /(BO3 +F) group disorder is found; 46 % of the sites being occupied by BO4 groups and 54 % by BO3 groups, with a fluoride ion located near the missing oxygen atom. The rare earth cations in the 4 f sites exhibit a specific distorted tricapped trigonal prismatic coordination with a mean metaprism twist angle of 21.3°. The crystal structure of Pr5 (BO4 )3− x (BO3 ) x (F, OH)2.67 O0.28 ( x ≈1.6) shows much "flexibility" resulting in split and off‐site positions of all other rare earth cations. The title compound therefore combines many structural features of apatite‐like compounds, for example biologically highly‐important carbonated apatites, shedding more light onto the complex structural chemistry of apatites. Abstract : The apatite superstructure of Pr5 (BO4 )3− x (BO3 ) x (F, OH)2.67 O0.28 ( x ≈1.6) is based on a tripling of the unit cell, due to partial ordering of the complex anion disorder along the 63 screw axis and BO4 /(BO3 +F) group disorder. It thereby combines structural features solely found in different apatite‐type compounds up to now, including the PO4 /CO3 group disorder in nonstoichiometric carbonated apatites, the main mineral components of human and animal hard tissue in bone and teeth.